Pocket book of integrals and mathematical formulas - Tallarida, Ronald J. (Boca Raton : CRC Press, 2008)
This handy, compact reference describes mathematical concepts and formulas for engineering, science, applied math, and statistics. It includes information on topics from precalculus to vector analysis and Fourier transforms to statistics.
Keywords: Integrals -- Tables; Mathematics -- Tables